The Impact of the Economic Corridor on Economic Stability: A Double Mediating Role of Environmental Sustainability and Sustainable Development Under the Exceptional Circumstances of COVID-19 - Li, Haiyan; Hameed, Javaria; Khuhro, Rafique Ahmed; Albasher, Gadah; Alqahtani, Wedad; Sadiq, Muhammad Waqas; Wu, Tong (Frontiers in Psychology, 2021)
This study discusses impact of different economic indicators on economic stability, including honest leadership, improved infrastructure, revenue generation, CPEC while the double mediating role of environmental sustainability and sustainable development, while considering the latest COVID-19 situation. This study adopted the primary data collection methods and got the data from the employees of CPEC by using questionnaires and smart-PLS for analysis purposes. The results revealed that honest leadership, improved infrastructure, revenue generation, and CPEC have positive nexus with economic stability. Despite the severe impact of COVID-19 on the country's economy, the economic corridor plays a vital role in stabilizing the state's economy and supports all those related to this phenomenal project either directly or indirectly.